The Relationship Between Characteristic of Tuberculosis Patient with Compliance in Check a Sputum During Treatment - Dea Nurma Ruditya (Jurnal Berkala Epidemiologi, 2015)
Pulmonary Tuberculosis (TB) in Indonesia is one of the national priorities for disease control programs. The cure rate and treatment success in the Public health center (PHC) of Tanah Kalikedinding is still not reaching the target. This study was conducted to determine the relationship between age, sex, education level, employment status, and income level of pulmonary TB patients with TB patient compliance in sputum examination during treatment in the PHC of Tanah Kalikedinding, Surabaya. This research was an observational analytic study with a cross-sectional design. Data were obtained on 38 respondents of pulmonary TB positive acid-resistant bacteria (BTA+) (category 1) aged 15–65 years who had completed treatment for 6 months from January 2012 to June 2013. Sampling used a simple random sampling technique. The independent variables studied were the characteristic variables namely age, sex, education level, employment status, and income level while the dependent variable was the compliance variable examining sputum during treatment. Data were analyzed using the chi-square test and multiple logistic regression. The results showed that age (p = 0.699), sex (p = 0.446), level of education (p = 0.712), employment status (p = 1.00), and income level (p = 0.48) were not related to TB patient compliance in sputum examination during treatment. It is necessary to conduct a home visit program by health personnel for patients who are not compliant to check phlegm and conduct further research for health service factors.